أدوار كليات التربية النوعية في مجال خدمة المجتمع وتنمية البيئة في ضوء رؤية مصر 2030 م.: كلية التربية النوعية جامعة طنطا نموذجا - العصامي، عبير فوزي عبدالفتاح Alessami, Abir Fawzi Abdulfattah (جامعة عين شمس - كلية التربية, 2020)
هدفت الدراسة الحالية إلى الكشف عن أدوار كليات التربية النوعية في مجال خدمة المجتمع وتنمية البيئة، واستخدمت الدراسة المنهج الوصفي المسحي, وأداة الاستبانة، والتي تم تطبيقها على عينة عشوائية طبقية بلغ عددها (69) عضوا من أعضاء هيئة التدريس بكلية التربية النوعية جامعة طنط ا، وتوصلت الدراسة الى نتائج أهمها؛ درجة التوفر على إجمالي المحاور (كبيرة) من وجهة نظر عينة الدراسة، حيث جاء المحور الرابع الخاص بأدوار كليات التربية النوعية في نشر الثقافة العامة بالمجتمع في المرتبة الأولى بنسبة استجابة (86.31 %) وهي درجة موافقة كبيرة، وفي المرتبة الثانية المحور الثالث الخاص بأدوار كليات التربية النوعية في نشر الوعي البيئي بالمجتمع بنسبة استجابة (80.11 %) وهي درجة موافقة كبيرة ، ثم جاء المحور الأول الخاص بأدوار كليات التربية النوعية في إعداد القوى البشرية المدربة والمؤهلة لإحداث تنمية بالمجتمع في المرتبة الثالثة بنسبة استجابة (78.38 %) وهي درجة موافقة كبيرة، وفي المرتبة الرابعة والأخيرة المحور الثاني الخاص بأدوار كليات التربية النوعية في ترقية البحث العلمي لخدمة المجتمع والبيئة بنسبة استجابة (78.03 %) وهي درجة موافقة كبيرة .
The current study aimed to uncover the roles of Specific Education Faculties in the field of community service and environmental development. The study used the descriptive survey method and the questionnaire tool, which was applied to a stratified random sample of (69) members of the teaching staff at the Faculty of Specific Education, Tanta University. The study leads to results the most important of which are: The degree of availability of the total axes (large) from the point of view of the study sample, where the fourth axis related to the roles of specific education colleges in spreading general culture in society came first with a response rate of (86.31%), which is a large degree of approval. And in second place came the third axis which is related to the roles of specific education colleges in spreading environmental awareness in society with a response rate (80.11%), which is a great degree of approval, then came the first axis related to the roles of specific education colleges in preparing trained and qualified manpower to bring about development in society. (78.38%), which is a high degree of approval, and in the fourth and last place is the second axis for the roles of the Faculties of Specific Education in promoting scientific research to serve the community and the environment with a response rate (78.03%), which is a great degree of approval.
Keywords: الإدارة التعليمية -- مؤسسات التعليم العالي -- التربية النوعية -- خدمة المجتمع -- التنمية المستدامة -- التوقعات المستقبلية -- مصر